What Do We Value Most in Schools? A Study of Preference Rankings of School Attributes1. (1st November 2016) - Hassan, Mamdouh; Geys, Benny
Abstract : Objectives: A key question in education policy as well as individuals' school choice involves the characteristics of schools we value most. It is thereby important to understand any heterogeneity in parents', teachers', and school principals' preference rankings driven by their education level, gender, and age. Method: In this article, we propose a survey‐based approach to examine preference rankings of diverse school attributes, which accounts for tradeoffs required in real‐world choice situations. Results: Our results indicate that stakeholders on average rank the "ethical" aspects of schools (such as pupil and staff happiness and equality of opportunities) above their "efficiency" aspects (such as academic achievement or school size). Yet, respondents' role in the school as well as their education level, gender, and age influence observed preference rankings. Conclusions: To avoid biased inferences, survey designs on school preferences should account for the fact that real‐world choices in favor of one particular characteristic often imply giving up at least some others. Doing so, we show that parents, teachers, and school principals appear to disagree with the predominant consideration awarded to academic achievement in current education policies.